2X2 waveguide based thermooptic photonic switch - Abu Sahmah Mohd. Supa'at, author; Abu Bakar Mohammad, 1959-, author; N. M. Kassim, author; Sevia Mahdaliza Idrus, 1974-, author; Young Optical Scientist Conference (2009 : Moscow, Russia) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL